If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8n + (1 + 5n) = -6n Remove parenthesis around (1 + 5n) -8n + 1 + 5n = -6n Reorder the terms: 1 + -8n + 5n = -6n Combine like terms: -8n + 5n = -3n 1 + -3n = -6n Solving 1 + -3n = -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. 1 + -3n + 6n = -6n + 6n Combine like terms: -3n + 6n = 3n 1 + 3n = -6n + 6n Combine like terms: -6n + 6n = 0 1 + 3n = 0 Add '-1' to each side of the equation. 1 + -1 + 3n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3n = 0 + -1 3n = 0 + -1 Combine like terms: 0 + -1 = -1 3n = -1 Divide each side by '3'. n = -0.3333333333 Simplifying n = -0.3333333333
| K+0.6=3.84 | | -x-3=3x+33 | | (8m-8n)(4m-7n)= | | 8x+7x-88=110-7x | | -3x-(-5)+2x=-x-4 | | 1+5x-40=1x-5 | | x+x+4=36 | | -10+x+4-4-5=7x-5 | | 6x+2(7x-4)=92 | | x+2y=29 | | -3x+8=18+4x | | x+2x=62 | | x-3(x-4)+2=14-3(5x+6) | | 3*n-8=2*n+15 | | 4(6x+3x)=12 | | 60k+60k=50k+100 | | x+x+2=62 | | -9+2.5y-.7y+1+6.4y= | | 2.4x=4x-88 | | X^2+5x=46 | | xy-d=mfory | | -18+9x=63 | | 2(x+4)+3(-x)=2(-x) | | -x+1=3x+21 | | 6X-1Y=18 | | 2(4c-1)=8c-2 | | x-2x-3=-x+9 | | 2s+8=22 | | 3(5x-4)-8x=7x-12 | | -7x+14=49-2x | | 10y+8x=314 | | 5y-3=2y-6 |